Graphene supported bimetallic G-Co-Pt nanohybrid catalyst for enhanced and cost effective hydrogen generation - Saha, S. (Elsevier Ltd, 2014)
A highly active and stable bimetallic nano-hybrid catalyst Graphene-Cobalt-Platinum (G-Co-Pt) is proposed for the enhanced and cost effective generation of hydrogen from Sodium Borohydride. Three different nano-hybrid catalysts namely Graphene-Cobalt (G-Co), Graphene-Platinum (G-Pt) and Graphene-Cobalt-Platinum (G-Co-Pt) are synthesized, characterized using XRD, FTIR, SEM, HRTEM, EDAX and Cyclic voltammetry (CV) analysis and tested for hydrogen generation. The activity and stability of the catalysts are analyzed by estimating the turnover frequency (TOF), the electrochemically active surface area (ECSA), the percentage decay of current density over ten cycles of CV and the decay in the rate of hydrogen generation with the age of catalyst. Among the three catalysts G-Co-Pt exhibits the highest catalytic activity (TOF = 107 min-1, ECSA = 75.32 m2/gm) and stability. The evaluated value of activation energy of the catalytic hydrolysis using G-Co-Pt is 16 Â± 2 kJ mol-1. Copyright Â© 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.